2022
DOI: 10.1111/ppc.13128
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychological capital in the relationship between nurses' job satisfaction and turnover intention

Abstract: Purpose: To find out whether psychological capital has a mediating role in the relationship between job satisfaction and turnover intention on nurses.Design and Methods: This study is a cross-sectional descriptive study. 466 nurses participated in this study. Data were collected via paper-and-pencil format using Minnesota Satisfaction Questionnaire, Psychological Capital Questionnaire and Turnover Intention Scale.Conclusions: Our findings revealed effects of poor psychological capital among nurses. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…On the other hand, different studies indicate that healthcare professionals are exposed to challenging and uncertain environments; therefore, the development of psychological capital becomes crucial for the affective commitment of these professionals [2,30]). Furthermore, previous research has shown positive and significant results between psychological capital and affective commitment [73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, different studies indicate that healthcare professionals are exposed to challenging and uncertain environments; therefore, the development of psychological capital becomes crucial for the affective commitment of these professionals [2,30]). Furthermore, previous research has shown positive and significant results between psychological capital and affective commitment [73].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of healthcare, previous studies have demonstrated a positive relationship between psychological capital and the Management of Clinical Psychological Stressors [27], reward satisfaction [28], well-being [25], mental health [18], work engagement [29], and job satisfaction [30]. However, more studies are needed to understand the relationship more comprehensively between psychological capital and other positive outcomes, especially the organizational commitment of healthcare professionals.…”
Section: Positive Psychological Capitalmentioning
confidence: 99%
“…The results indicated that the concept of PSR could provide insights into understanding the relationship between PsyCap and JobSat. Numerous academic investigations have yielded empirical data substantiating the existence of favorable associations between PsyCap and JobSat (Alan et al, 2022; Fu et al, 2013; Hansen et al, 2015; Larson & Luthans, 2006; Liu et al, 2018; Loghman et al, 2023; Luthans et al, 2007; Zhang et al, 2021). These results are a good reminder of how important a worker’s psychological resources and level of JobSat is.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have been conducted regarding turnover intention of nurses, the strongest predictor of nurses leaving the healthcare industry (3). Work-related factors including high job demand (4)(5)(6), job stress (7)(8)(9), job dissatisfaction (10)(11)(12), and low organizational commitment (13)(14)(15) have been blamed for triggering turnover intention of nurses apart from family commitment.…”
Section: Introductionmentioning
confidence: 99%